Biallelic Intronic AAGGG Expansion of RFC1 is Related to Multiple System Atrophy. Issue 6 (3rd October 2020) - Wan, Linlin; Chen, Zhao; Wan, Na; Liu, Mingjie; Xue, Jin; Chen, Hongsheng; Zhang, Youming; Peng, Yun; Tang, Zhichao; Gong, Yiqing; Yuan, Hongyu; Wang, Shang; et al.
Abstract : Objective: A recessive biallelic repeat expansion, (AAGGG)exp, in the RFC1 gene has been reported to be a frequent cause of late‐onset ataxia. For cerebellar ataxia, neuropathy, and vestibular areflexia syndrome (CANVAS), the recessive biallelic (AAGGG)exp genotype was present in 92% of cases. This study aimed to examine whether the pentanucleotide repeat (PNR) was related to multiple system atrophy (MSA), which shares a spectrum of symptoms with CANVAS. Methods: In this study, we screened the pathogenic (AAGGG)exp repeat and 5 other PNRs in 104 Chinese sporadic adult‐onset ataxia of unknown aetiology (SAOA) patients, 282 MSA patients, and 203 unaffected individuals. Multiple molecular genetic tests were used, including long‐range polymerase chain reaction (PCR), repeat‐primed PCR (RP‐PCR), Sanger sequencing, and Southern blot. Comprehensive clinical assessments were conducted, including neurological examination, neuroimaging, nerve electrophysiology, and examination of vestibular function. Results: We identified biallelic (AAGGG)exp in 1 SAOA patient and 3 MSA patients. Additionally, 1 MSA patient had the (AAGGG)exp /(AAAGG)exp genotype with uncertain pathogenicity. We also described the carrier frequency for different PNRs in our cohorts. Furthermore, we summarized the distinct phenotypes of affected patients, suggesting that biallelic (AAGGG)exp in RFC1 could be associated with MSA and should be screened routinely in the MSA diagnostic workflow. Interpretation: Our results expanded the clinical phenotypic spectrum of RFC1 ‐related disorders and raised the possibility that MSA might share the same genetic background as CANVAS, which is crucial for re‐evaluating the current CANVAS and MSA diagnostic criteria. ANN NEUROL 2020;88:1132–1143